Phytochemical Analysis, Antioxidant and Antimicrobial Screening of Seriphidium Oliverianum Plant Extracts. Issue 1 (30th March 2021) - Abbas, Ali; Naqvi, Syed Ali Raza; Rasool, Muhammad Hidayat; Noureen, Asma; Mubarik, Muhammad Samee; Tareen, Rasool Baksh
The aim of this study was to investigate the phytochemicals using reverse-phase high pressure liquid chromatography (RP-HPLC), antioxidant, antifungal and antibacterial activities of Seriphidium oliverianum stem extracts. The extraction was carried out by conventional shaking process (CSP) and ultrasonic assisted process (UAP). The highest total phenolic contents (97.85 ± 0.735 mg gallic acid equivalent (GAE)/g sample) and flavonoid contents (188.15 ± 0.53 mg catechin equivalent (CE)/g sample) were found in methanol extract obtained by CSP. Antioxidant activity was investigated using DPPH° scavenging assay and reducing power assay. Methanol extract using UAP showed the highest DPPH° scavenging activity (79.95% ± 1.80%) followed by methanol and butanol extracts obtained through CSP. Moreover, methanol extracts using CSP showed highest reducing activity (1.032 ± 0.0205 absorbance). In-vitro antimicrobial activity was studied using most common infection causing fungal and bacterial strains. Anti-fungal activity of methanol extract using CSP showed the highest zone of inhibition (10.5 mm) against F. avenaceum fungal strain, while aqueous extracts obtained through showed the highest antibacterial activity (22 ± 1.32 mm zone of inhibition) against S. aureus . The results showed that the methanol stem extract of S. oliverianum is a valued candidate for further screening and could be processed for in-vivo infection induced animal trials.